2017
DOI: 10.1039/c7sc03281a
|View full text |Cite
|
Sign up to set email alerts
|

Field-deployable, quantitative, rapid identification of active Ebola virus infection in unprocessed blood

Abstract: The West African Ebola virus outbreak underlined the importance of delivering mass diagnostic capability outside the clinical or primary care setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 73 publications
5
11
0
Order By: Relevance
“…in envenomation wounds (Garg et al 2009), and Blaylock's seminal snake oral flora studies also reported Proteus 5 and Staphylococcus (Blaylock 2001): both relied on the same methods we used that resulted in pathogen misidentification. Our results therefore further support use of PCR/sequencing methods as they become more relevant to resource limited settings (Quick et al 2016), and suited to the point of need (Shah et al 2017), in line with World Health Organisation ASSURED criteria.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…in envenomation wounds (Garg et al 2009), and Blaylock's seminal snake oral flora studies also reported Proteus 5 and Staphylococcus (Blaylock 2001): both relied on the same methods we used that resulted in pathogen misidentification. Our results therefore further support use of PCR/sequencing methods as they become more relevant to resource limited settings (Quick et al 2016), and suited to the point of need (Shah et al 2017), in line with World Health Organisation ASSURED criteria.…”
Section: Discussionsupporting
confidence: 75%
“…in envenomation wounds (12), and Blaylock's seminal snake oral flora studies also reported Proteus and Staphylococcus (14): both relied on the same methods we used in this study that were found to misidentify the pathogen. Our results therefore further support use of PCR/sequencing methods as they become more relevant to resource limited settings (53), and suited to the point of need (54), in line with World Health Organisation ASSURED criteria. Understanding the sensitivity of these methods will be crucial in their reliable implementation in envenomation care.…”
Section: Discussionsupporting
confidence: 75%
“…FDA EUA. QuRapID platform [ 53 ] In blood RT-qPCR (far red dyes), use in resource poor regions. 20 kg, table top device, car alternator/battery or mains capable.…”
Section: Diagnosticsmentioning
confidence: 99%
“…The QuRapID system uses these dyes in addition to rapid freeze/thaw cycles to isolate and then amplify viral RNA. The 20 kg stand-alone system has been developed for field use [ 53 ]. Two bead-based PCR assays were developed to detect multiple RNA viruses from bat urine [ 54 ].…”
Section: Diagnosticsmentioning
confidence: 99%
“…Infectious diseases are among the most critical global health problems. 1,2 Current and rapidly evolving public health threats from HIV to emerging pathogens, including the ongoing pandemic of COVID-19, have impelled urgent needs of sensitive, fast and cost-effective techniques for nucleic acid detection (NAD). [3][4][5][6] Digital NAD (dNAD) techniques hold promise for highprecision, high-sensitivity and absolute quantication of pathogens.…”
Section: Introductionmentioning
confidence: 99%